Stosunki irańsko-tureckie na początku XXI wieku: implikacje dla regionu Bliskiego Wschodu - Osiewicz, Przemysław (Przegląd Strategiczny, 2011)
Both Turkey and Iran are perceived as regional powers of the Middle East. Although Saudi Arabia and Egypt are also key players in the region, Iran and Turkey have tremendous potential in terms of politics, economy, demography as well as military power. This article is dedicated to the analysis of Turkish Iranian relations at the beginning of the 21st Century. Undoubtedly, current political and economic rapprochement between these two states is noticeable. Yet the most important questions concern the reasons for it as well as possible implications for the Middle East.